A DECADE FROM THE MAJOR LAYOFFS IN THE JIU VALLEY - IOAN VALENTIN FULGER; ION HIRGHIDUS; EVA BOCSA (Annals of the University of Petrosani: Economics)
This essay is an overview of how the population of the largest coalfield of Romania Jiu Valley, the perceived major staff cuts in the mining industry, the solutions required for economic rehabilitation of the area and difficulties of everyday faced by residents of the region.